Envelope or triangular flap for surgical removal of third molars? A systematic review and meta-analysis. Issue 8 (August 2020) - Lopes da Silva, B.C.; Machado, G.F.; Primo Miranda, E.F.; Galvão, E.L.; Falci, S.G.M.
Abstract: The aim of this systematic review was to compare the triangular and envelope flaps in mandibular third molar surgery with regard to pain, oedema, and trismus. Secondary outcomes assessed were dehiscence, ecchymosis, alveolar osteitis, periodontal condition, and surgical time. The PRISMA guidelines and recommendations in the Cochrane Handbook were followed, and the review was registered before commencement (PROSPERO; CRD42018112373). The literature search was conducted in the Web of Science, PubMed, Virtual Health Library, Cochrane Library, and Scopus databases and in the grey literature; randomized clinical trials, indexed through November 2018 were included. Three reviewers independently examined the studies. Twenty studies were included in the qualitative analysis, of which 18 were included in the meta-analyses. The flap design did not influence pain, oedema, trismus, dehiscence, or osteitis. The triangular flap was associated with a greater occurrence of postoperative ecchymosis (odds ratio 4.58, 95% confidence interval 1.34 to 15.91, I 2  = 0) and lower periodontal probing depth on day 7 postoperative (standardized mean difference −1.36, 95% confidence interval −2.68 to −0.03, I 2  = 88%) when compared to the envelope flap in mandibular third molar surgeries.